What Are The Sentiments of Instagram Netizens @Perempuanberkisah About The Issue Of Sextortion? - Hasugian, Tesalonika; Girsang, Lasmery RM (Journal of Dialogos, 2024)
Social media provides space for perpetrators to commit sexual violence online. Especially regarding the gap in society's views on gender patriarchy. Sextortion, in cases of sexual violence for personal gain, is in the spotlight in understanding gender inequality. This qualitative research seeks to explore the sentiment of public comments regarding sextortion content using the Atlas ti software mechanism. The data collected consists of comments from Instagram users regarding the issue of sextortion. Perempuan Bercerita's Community posted about a sextortion case on Instagram on February 27th, 2023. The content discussed the threats made by the perpetrator, involving sexual relations and the distribution of pornographic videos targeting female victims. The analysis results indicate a total of 54 comments consisting of 9% positive comments, 54% negative comments, and 37% neutral comments. Society still has a low opinion of digital sexual violence; and tends to judge the victim from the side of the action to the perpetrator. Future findings are expected to analyze more deeply the social interaction networks of digital society to understand society's social perspective on gender inequality.